Avaliação do estresse oxidativo e modulação autonômica cardiovascular pós-irradiação de laser de baixa intensidade em ratos espontaneamente hipertensos: estudo experimental - Tomimura, Suely (2013)
Due to the increasing numbers of Systemic Arterial Hypertension (HBP) patients in population and its senescence, steadily increased from 600 million in 1980 to 1.2 billion in 2008. The World Health Organization (WHO) in 2009 attributed to high blood pressure (BP) was the death cause for 9.5 million people worldwide. Currently, the hypertension has become a serious public health problem. This entity is an important risk factor for congestive heart failure, cerebrovascular disease, acute myocardial infarction, nephropathy, retinopathy and peripheral vascular insufficiency. Studies have suggested that laser photobiomulation, employing a low power, acts into the inflammatory and proliferative phases of tissue repair, by modulating the inflammatory mediators synthesis as same as the Reactive Oxygen Species (ROS). According scientific publications indicate that the inflammation component is closely related to systemic arterial hypertension as well as possibly to the oxidative stress, both participates in the Hypertension genesis. The aim of this study was to verify the long-term effects of Low Level Laser Therapy (LLLT) application in Spontaneously Hypertensive Rats-SHR (Spontaneously Hypertensive Rats) through on cardiovascular autonomic modulation and oxidative stress in the blood. The experiment consisted in 3 phases: Phase I – LLLT irradiation on SHR: The experiment's phase I consisted of animal’s irradiation, when the laser group received three times LLLT applications weekly for a 7 weeks total; the sham group received three times per week of LLLT simulation for 7 weeks and a total of 21 applications. Prospective, randomized, controlled study, with 16 SHR approximately 2 months age, randomly divided into 2 groups : Sham (n = 8) and Laser (n = 8). The animals were irradiated in a prompt, onto the tail’s dorsal area, using a Diode Laser (MMOptics, São Carlos, SP, Brazil) with a wavelength (λ) of 780 ± 2 (nm), output power at 40 mW, with a 0.04 cm2 beam area, dose of 30 J/cm2 power density of 1W/cm2 and irradiation time of 90 s. In Phase II - Hemodynamic and autonomic cardiovascular evaluation: for a period of 7 weeks, consisted in the cannulation procedure, collecting and analysis. The animals were cannulated, evaluated hemodynamically and analyzed the cardiovascular autonomic modulation. Phase III - Oxidative stress analysis, were analyzed: a) protein damage; b) cell membrane damage; c) antioxidant enzyme activity; d) nitrite concentrations. Data from phase II and III were collected and statistically analyzed applying One Way ANOVA test, followed by post hoc Student - Newman Keulls and considering the significance level of p < 0.05, equivalent to an error α 0.05. The results demonstraded hemodynamic parameters of group LLLT treated showed a BP reduction, when compared with the Sham group. In laser group the diastolic arterial pressure (DAP) showed a reduction of -14 mmHg (± 143 * 4 x 157 ± 3 mmHg Sham) and mean arterial pressure (MAP) - 13mmHg (169 ± 4 * x 182 ± 4 mmHg Sham) there were statistically significant difference. Although the value of systolic arterial pressure (SAP) (196 ± 5 x 207 ± 4 mmHg) showed no differences. There was a decreased in resting HR with a statistically significant difference in the laser group compared to Sham (312 ± 14 vs. 361 ± 13 bpm sham). The spectral reviews in the field of time and frequency showed that the Laser group decreased sympathetic activity on the heart and blood vessels while compared to the Sham group. The heart rate variation was analyzed using the DP-PI ( standard deviation of the pulse interval) VAR-PI components (pulse interval variability) and it demonstrated that LLLT was effective in diminishing variation in heart rate (HR) and sympathetic activity in heart, inducing a substantial fall in blood pressure. Lasertherapy presented a rise in spectral low-frequency component in the pulse interval (LF - IP action of the sympathetic at heart), though the sham group showed up exaggeratedly decreasing (6.77 ± 4:35 and 2:31 ± 0:16 ms ² Sham) as a function of saturation variation. Thus, there was a significant reduction in sympathetic activity after LLLT using. A high-frequency band on interval pulse HF-IP (parasympathetic activity) showed no statistically significant differences between the groups and Laser Sham group. The baroreceptor sensitivity, assessed by the alpha index, signalized a significant increase in the Laser (1:07 ± 0:23 vs. 0:45 ± 0:20 ms / mmHg Sham) group, presenting an improvement in the receptors sensitivity. The baroreflex results were associated with other relevant data, the VAR - SAP (49.55 ± 15.94 * vs 70.51 ± 13:55 mmHg² Sham) and SD -SAP (6.94 ± 1.21 * vs 8.68 ± 1.11 mmHg Sham) that proved to be diminished in the laser group, indicating baroreflex improvement sensitivity concomitantly to the positive SAP variation reduction of. There were no significant differences in baseline SAP (196 ± 5 vs. 207 ± 4 mmHg Sham) between the two groups. The results in the oxidative stress and autonomic analysis demonstrated an association between increased NO production (nitrite 0:36 ± 0:03 vs 0:26 ± 0:03 nm / mg Sham) and decreased in the vascular sympathetic (LF - SAP 7.28 ± 1.63 * vs 9.86 ± 0.47 Sham), both leading to a profound vasodilatation then a significant fall in of blood pressure. Lasertherapy shown to alter the plasma parameters such as oxidative nitrite, revealing an NO increased metabolism, as described above and, moreover, accounted for a significant reduction in carbonyl plasma concentration (vs 3.93 ± 0.24, 4.75 ± 0:26 * nm / mg Sham). Our experimental study indicate that LLLT was able to reduce the oxidative stress parameters through diminishing the damage to the proteins. The enzymatic defense was analyzed by the enzyme SOD concentration in blood plasma, denoted that no significant differences (4:42 ± 0:10 4:25 ± 0:06 vs usod / mg) between groups. Thus, low level laser therapy has shown to improve cardiovascular autonomic activity as well as oxidative parameters which resulted in steadily staggeringly reduce the blood pressure of hypertensive animals.